Empowerment of Fish Farming Groups through Strengthening Business Management and Digital Marketing Strategy - Andi Agung Hariawan Patempoi; Aminuddin; Herwandi Sape; Muhammad Fuad; A. Rahmatia; Muh. Ilham; Savira Jumriany Amaliah (ITEKES Permata Ilmu Maros, 2026)
Small-scale fish farming groups in South Sulawesi commonly face two persistent constraints: weak business management practices and limited access to modern marketing channels. This community service program aimed to strengthen the business management capacity and digital marketing skills of UPR Kurnia Baku, a fish-seed cultivation group in Dusun Baku, Desa Lekopancing, Kecamatan Tanralili, Kabupaten Maros. The program involved 20 members of the partner group and was carried out through counseling, hands-on training, and mentoring covering simple bookkeeping, cash-flow planning, product branding, and the use of social media and e-commerce platforms for marketing. Activities were implemented in three stages: pre-activity preparation, the core training and mentoring session, and monitoring and evaluation using questionnaires and direct observation. The results showed a marked increase in participants' understanding of financial recording, business planning, and digital promotion techniques, with average scores rising from 52 to 81 (of 100) for business management and from 46 to 78 (of 100) for digital marketing, along with growing confidence in using smartphones and social media applications to market fish-seed products. Members also began preparing simple financial records and product catalogues for online promotion. The program is expected to encourage UPR Kurnia Baku toward more structured business management and a wider market reach, ultimately improving group income and long-term business sustainability. Continued mentoring and periodic evaluation are recommended to sustain these improvements and expand digital adoption among members.